Simple Oxidation of Benzylic Halides with 1-Butyl-3-methyl Imidazolium Periodate - Heidarizadeh, Fariba; Asareh, Haadii (Asian Journal of Chemistry, 2010)
Radical halogenation at the benzylic position, followed by the oxidation of the resulting halide is one of the most practical methods leading to the formation of desired carbonyl compounds. Thus, an efficient method for this oxidation conversion with the help of ionic liquid. A variety of benzyl halides with different substituent were converted to the corresponding aldehydes by 1-butyl-3-methyl imidazolium periodate at room temperature in high yields.